Is it possible (and desirable) to democratize barbarism? Marxist contributions to Political Psychology - Farias, Tadeu; Costa, Pedro; Vieira, André (Journal Studies of Public Policy, 2022)
We seek to reflect on the contributions of political psychology to Brazilian reality, from Marxian and Marxist theoretical-methodological framework. We take as justification the situation of structural crisis of capitalism, the neoliberal advance and its economic, social, political and ideological consequences, as well as its expressions in/by political psychology. We analyze how the structure of production-distribution of social wealth, in guaranteeing the private ownership of the means of production, and the role of the State in this, establish a concrete limit for the realization of human values and rights. Marxism equips us not only for the critique of political psychology, but for its critical use, aiming its own overcoming. We consider, therefore, that political psychology can be important if and as long as (self)criticism and as a demarcation of the limitations of hegemonic psychology, seeking to stress psychology and transform it, and contribute to overcoming the very milestones of bourgeois democracy.